The opinions of farm animal veterinarians in Ireland on antibiotic use and their role in antimicrobial stewardship - Sorcha O’Connor; Simon J. More; David C. Speksnijder; Carloalberto Petti (Irish Veterinary Journal, 2023)
Abstract Background Antibiotic use and resistance in animal production are a concern to public health, and there is an urgent need to reduce antibiotic use in farm animals. To prevent blame shifting, professionals from human medicine, animal medicine and environmental backgrounds must collaborate to tackle this issue. Veterinarians are typically responsible for overseeing and prescribing antibiotic use in animals. There are currently no available studies on the opinions of Irish farm animal veterinarians on antibiotic use, reduction opportunities and their relationships with farmers. A digital survey was developed and sent out to Irish farm animal veterinarians. This paper presents the results of a cross-sectional study of Irish farm animal veterinarians’ attitudes towards antimicrobial stewardship, their prescribing behaviours, antibiotic reduction opportunities and their attitudes for the future of antibiotic use. The veterinarian-farmer relationship is examined and potential interventions to reduce antibiotic use on farms are identified. Results In total, 114 complete questionnaires were received, representing approximately 11 per cent of all farm animal veterinarians in Ireland. Respondents were aware of the problem of antibiotic resistance and recognise their role in the fight against it. They realise what actions they must take to reduce antibiotic use and identify barriers that prevent their farmer clients from implementing their advice. Many of them say that they can reduce antibiotic use on farms in the future, but some remain doubtful. There was no statistical difference between veterinarians that had less experience working than those that had more experience in their attitudes towards future reduction in antibiotic use. Conclusion Most of the respondents seek to use antibiotics as judiciously as they can. The majority agree that antibiotic overuse is the main contributor to antibiotic resistance. Possible solutions to reduce antibiotic use include the development of antibiotic treatment guidelines, assigning one unique practice to each farm and compulsory CPD (Continuous Professional Development) courses.